Analysis of the Impact of Curriculum Change Policy on the Performance of Junior High School Teachers in Hamparan Perak District - Nazura, Nana Nazwana; Syahriani, Anggun; Syarif, Mujahid (Yayasan Rahmat Islamiyah, 2025)
This study aims to analyze the impact of curriculum change policy on the performance of Junior High School teachers in Hamparan Perak District. The research employed a quantitative approach using survey techniques. Data were collected through questionnaires distributed to teachers from both public and private junior high schools. The findings indicate that curriculum changes significantly affect teacher performance in terms of lesson planning, instructional delivery, and student assessment. While some teachers showed improved professionalism due to the demands of the new curriculum, others struggled to adapt to the rapid and complex changes. Therefore, continuous training and mentoring are necessary to support teachers in effectively implementing the new curriculum.